(untitled) (Práxis Educativa, 2024)
This article aimed to systematize and analyze the documents that guide the educational transformation processes in the Uruguayan educational system, which began in 2020. To this end, the content of nine official documents related to Comprehensive Curricular Transformation was examined, based on three theoretical dimensions: epistemological, pedagogical and institutional, and the theory of critical transitions. The results show that the documents propose a curricular vision based on the development of skills and learning, which requires changes in teaching methodologies, teaching strategies and assessment. Similarly, it is proposed a school management that promotes the autonomy and participation of educational communities. It is concluded that Educational Transformation is a complex and dynamic process, which involves challenges and opportunities for improving educational quality. Some recommendations are suggested to address critical transitions that may arise in implementing changes. Keywords: Educational transformation. Curriculum. Skills. Uruguay.